Tevah dan Tipologi Kristus dalam Perjanjian Lama - Anon Dwi Saputro; Yokibet Henny Kawangung (Phronesis: Jurnal Teologi dan Misi, 2025)
The Hebrew term תֵּבָה (tevah) is a rare expression in the Old Testament, occurring only in the narratives of Noah’s Ark (Gen. 6–9) and the infant Moses’ basket (Exod. 2:3, 5). This scarcity indicates both literary intentionality and a distinctive theological function. The purpose of this study is to examine tevah as a motif of salvation through intertextual and typological approaches, by analyzing the interconnection of these two narratives and their implications for the theology of salvation. The method employed is word study with semantic analysis, textual exposition, and canonically oriented typological reading. The findings reveal that tevah consistently appears in contexts where water represents the threat of death, yet functions as a divinely appointed means of deliverance: in Noah’s account, the tevah preserves humanity and creation, whereas in Moses’ account, the tevah preserves the life of a leader destined to deliver Israel. The intertextuality of the two underscores the continuity of God’s saving work that reaches its fulfillment in Christ, whereby tevah may be read as a Christological typology of salvation This study affirms that the motif of tevah unites the narrative of salvation from the Flood to the Nile, forming a theologically relevant pattern for both biblical interpretation and church mission practice, while also demonstrating the continuity of God’s saving work, which finds its fulfillment in Christ.